Investigation of Altered Spontaneous Brain Activities in Patients With Moyamoya Disease Using Percent Amplitude of Fluctuation Method: A Resting-State Functional MRI Study - Li, Chu-Qi; Ge, Qian-Min; Shu, Hui-Ye; Liao, Xu-Lin; Pan, Yi-Cong; Wu, Jie-Li; Su, Ting; Zhang, Li-Juan; Liang, Rong-Bin; Shao, Yi; Zeng, Er-Ming (Frontiers in Neurology, 2021)
Background: Moyamoya disease (MMD) is a chronic progressive cerebrovascular abnormality characterized by chronic occlusion of large intracranial vessels with smoky vascular development at the base of the skull. In patients with MMD, abnormal spontaneous brain activity would be expected. Purpose: To assess the brain activity changes in patients with MMD by resting-state functional MRI (rs-fMRI), using the percent amplitude of fluctuation (PerAF) analysis method. Materials and Methods: A total of 17 patients with MMD (3 males and 14 females) and 17 healthy control (HC) subjects with matched gender and age were recruited for this study. We used rs-fMRI to scan all the patients with MMD. Spontaneous neural activity was evaluated using the PerAF approach. The receiver operating characteristic (ROC) curve analysis was used to assess the ability of the PerAF to distinguish patients with MMD from HCs. The Hospital Anxiety and Depression Scale (HADS) tests were performed to assess the emotional status of patients with MMD and retinal nerve fiber layer thickness (RNFLT) was measured using high-resolution optical coherence tomography (hr-OCT). The relationship between the HADS scores, RNFLT values, and the PerAF signals was assessed using the Pearson's correlation analysis. Results: Compared with HCs, the PerAF signals in patients with MMD were decreased in the Frontal_Sup_Medial_R and Precentral_L, whereas those in the Caudate_L were increased. The areas under the ROC curves indicated that signals in these brain regions could distinguish between patients with MMD and HCs. The PerAF value of Frontal_Sup_Medial_R was positively correlated with the left and right eye RNFLT values and negatively correlated with the HADS scores. Conclusion: In patients with MMD, reduced PerAF signals in the Frontal_Sup_Medial_R, Precentral_L, and Caudate_L may be associated with psychiatric diseases including anxiety and depression and decreased RNFLT may be associated with ophthalmic complications due to the compression of terminal branches of the internal carotid artery in the retinal fiber layer. The PerAF can be used as an effective indicator of ocular complications of MMD and to study the neural mechanism underpinning emotional complications in patients with MMD.